Research of Powertrain Control based on Power Shift Strategy - Mo Chongxiang; Wu Jian; Li Dianpeng (Jixie chuandong)
In order to solve the vehicle power discontinued transmission which influenced by the shift of the automated mechanical transmission and improve the shift quality,a new powertrain control strategy based on power shift is put forward. The traditional and hybrid powertrain interface based on this new strategy is designed. According to the result of the simulation and actual test,the comfort of driving and the continuity of power are obviously improved based on the power shift control strategy.